Exploring the Students’ Attention Level in Teaching and Learning of English - Risti Trias Yuliani; Made Adi Andayani T; Eka Wahjuningsih (Institut Agama Islam Negeri Palopo, 2022)
This research investigated the students' attention level in teaching and learning of English. The purposes of this research were to find out the students’ attention level and to find out the most dominant factor affecting the students’attention in teaching and learning of English. This research used a descriptive design with questionnaires as the data collection method. The researcher distributed the questionnaires at the end of English class. The data collected through the questionnaires were analyzed by using Walizer's (1990) formula to answer the research questions. In this research, the result showed that the level of students' attention in teaching and learning of English was at the moderate level and the most dominant factor affecting students' attention was the internal factor.